2004
DOI: 10.1159/000078105
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serum and Glucocorticoid Regulated Kinase (sgk1) Gene with QT Interval

Abstract: The serum and glucocorticoid inducible kinase (SGK1) is well known to up-regulate the renal epithelial Na+ channel ENaC. Excessive SGK1 activity would be expected to cause renal Na+ retention and blood pressure increase. Certain polymorphisms of the SGK1 gene (E8CC/CT;I6CC) are indeed associated with moderately enhanced blood pressure. We have recently disclosed another function of SGK1, i.e. the stimulation of the slowly activating K+ channel KCNE1/KCNQ1. Among the functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 64 publications
2
48
1
Order By: Relevance
“…For example, it has been reported that psychosocial stress plays a role in otherwise unexplained cardiac arrest (39). Furthermore, a gain-of-function SGK1 mutation has been reported in twins who displayed the shortened QT interval, which induces arrhythmias and sudden death (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that psychosocial stress plays a role in otherwise unexplained cardiac arrest (39). Furthermore, a gain-of-function SGK1 mutation has been reported in twins who displayed the shortened QT interval, which induces arrhythmias and sudden death (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The increased body mass index may partially be due to enhanced stimulation of the intestinal glucose transporter SGLT1 (25), the accelerated cardiac repolarization being due to enhanced activation of the cardiac K ϩ channel KCNE1 (17,29). Thus altered regulation of carriers and channels by SGK1 could account for the coincidence of obesity, hypertension, and altered cardiac action potential (45).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its effect on nutrient transporters, SGK1 is a potent regulator of renal electrolyte transporters, such as the epithelial Na ϩ channel ENaC (2,17,23,26,27,32,57,73,81,84), the renal K ϩ channels ROMK (60,87,91) and KCNE1/KCNQ1 (22,30), the epithelial Ca 2ϩ channel TRPV5 (31, 58), the Na ϩ /H ϩ exchanger NHE3 (89,90), the Na ϩ -K ϩ -2Cl Ϫ cotransporter NKCC2, and the Na ϩ -K ϩ -ATPase (39,69,92). SGK1 contributes to the effect of aldosterone, IGF-1, and insulin on ENaC activity and thus renal salt reabsorption (7)(8)(9)(10)84).…”
mentioning
confidence: 99%
“…SGK1 contributes to the effect of aldosterone, IGF-1, and insulin on ENaC activity and thus renal salt reabsorption (7)(8)(9)(10)84). A gene variant of the SGK1 gene is associated with increased blood pressure (21,22,80) and obesity (28). Therefore, SGK1 has been suggested as a candidate for the development of metabolic syndrome (46).…”
mentioning
confidence: 99%